The politics of sport funding in Brazil: a multiple streams analysis - Camargo, P.; Piggin, J.; Mezzadri, F. (International Journal of Sport Policy and Politics, 2020)
Since the earliest State interventions in sports, the Brazilian State has assumed the role of overseeing and financing the nation`s organised sport systems. The significant relationship between the State and sport, established over decades, contributed to sport being influenced by the country`s political agenda, influencing the implementation of sport funding policies. In order to understand more about how this relationship developed, this article applies the multiple streams theory of policy change to examine the Brazilian high-performance sport policy domain. Policy analysis and media analysis are combined to examine the ways in which the political context, problem framing and policy solutions were brought together by a range of policy entrepreneurs. The study examines how the Brazilian Olympic Committee (BOC) lobby effort acted to expand investment possibilities, and how policymakers acted swiftly to seize the window of opportunity and implement policies that stimulated Brazilian preparation for the Olympic and Paralympic Games in 2016. The article suggests that while other countries have also developed policies for elite sport to boost Olympic preparation, Brazilian policy decisions and changes were tardy, in some cases fleeting, and only expanded existing policies that had weaknesses in resource distribution criteria.